A COMPARISON OF DIFFERENT TEACHING APPROACHES AND THEIR IMPACT ON THE LEVEL OF THEORETICAL KNOWLEDGE OF VOLLEYBALL AMONG 13– 14-YEAR OLD PUPILS - Jaroslav Popelka; Ratko Pavlović (Sport Scientific And Practical Aspects, 2025)
In this paper the author deals with 13 – 14 year-old pupils’ theoretical knowledge of volleyball. The main method was pedagogical experiment. The evaluation was carried out using logical and mathematical-statistical methods. Through analysis of the questionnaire the author came to the conclusion that, when compared to the control group, the experimental group pupils achieved better results in the area of tactics questions. This result was of statistical significance (p<0.05). In the range of rules and technique questions he notes that the differences between groups were not of statistical significance (p>0.05).